Maurice Ravel: songs 1896-1914 - Orenstein, Arbie. 1937- (Colección Dover Orchestral Scores, 1990)
As a young composer in the years proceding World War I, Maurice Ravel Brought to the art of the song that distinctive fusion af classicism and the modern spirit that characterizad all his musical works and helped earn him a reputation as one of the most imoprtant modern French song composers.